The Effect of Inventory Intensity, Institutional Ownership, and Capital Intensity on Tax Avoidance: (Study on Non-Cyclical Consumer Sector Multinational Companies Listed on the IDX for the 2019-2023 Period) - Fachrezi Anantaprima; surifah (LP2M IAIN Palopo, 2025)
This study examined 70 consumer non-cyclical multinational companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, yielding a total of 350 observations, to investigate the impact of Inventory Intensity, Institutional Ownership, and Capital Intensity on tax avoidance. Utilizing a quantitative approach and the Random Effect Model (REM), the findings reveal that while Inventory Intensity and Capital Intensity do not have a significant effect on tax avoidance, Institutional Ownership exhibits a significant negative influence. Collectively, these three variables have a statistically significant impact on tax avoidance, accounting for 55.26% of its variation, as indicated by the adjusted R-squared value. These results underscore the critical role of institutional investors in curbing tax avoidance, highlighting the importance of strong corporate governance and transparent ownership structures. Future research is encouraged to incorporate external factors such as economic uncertainty or international tax regulations to provide a more comprehensive analysis.